2020
DOI: 10.1101/2020.08.04.20164061
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is Higher Viral Load in SARS-CoV-2 Associated With Death?

Abstract: There is no proven prognostic marker or adequate number of studies in patients hospitalized for Coronavirus Disease-2019 (COVID-19). We conducted a retrospective cohort study of patients hospitalized with COVID-19 from March 14 to June 17, 2020, at Sao Paulo Hospital. SARS-CoV-2 viral load was assessed using the cycle threshold (Ct) values obtained from an RTPCR assay applied to the nasopharyngeal swab samples. Disease severity and patient outcomes were compared. Among the 875 patients, 50.1% (439/875) had mil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 15 publications
(15 reference statements)
1
17
2
Order By: Relevance
“…Our findings demonstrate that the ∆ C t which was assumed to be inversely related to viral load were similar in all clinical courses and in all age groups in children with COVID‐19 in contrast to some previous reports, in which they reported that C t values were associated with disease severity 9,17 and even mortality 20,21 . On the other hand, limited number of studies reported any difference in median Ct values of groups with different symptom statuses, such as asymptomatic, presymptomatic, atypical, and typical symptoms 15,22 .…”
Section: Discussioncontrasting
confidence: 42%
“…Our findings demonstrate that the ∆ C t which was assumed to be inversely related to viral load were similar in all clinical courses and in all age groups in children with COVID‐19 in contrast to some previous reports, in which they reported that C t values were associated with disease severity 9,17 and even mortality 20,21 . On the other hand, limited number of studies reported any difference in median Ct values of groups with different symptom statuses, such as asymptomatic, presymptomatic, atypical, and typical symptoms 15,22 .…”
Section: Discussioncontrasting
confidence: 42%
“…In contrast, studies where a positive association between nasopharyngeal SARS-CoV-2 Ct values and COVID-19 severity or outcomes was detailed are flourishing [ 6 , 7 , 9 , 10 , 11 , 12 , 17 , 34 , 35 ]. Most of them included samples of more than 100 individuals with the reference swab represented by the diagnostic one, despite only two reported the time between disease onset and swab collection [ 7 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further to the recognized risk factors for severity, the initial prognostic workup of persons infected by SARS-CoV-2 would also benefit from viral biomarkers able to predict COVID-19 evolution. In this regard, it is a current matter of debate whether SARS-CoV-2 viral load is an impactful factor in determining disease outcomes [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Previous evidence from SARS-CoV and influenza suggests that the higher the initial viral load, the worse the clinical evolution [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggest using the Ct-value to identify patients with a high risk for severe clinical courses. Further studies also indicate that the viral load may serve as a surrogate marker of infectivity associated with mortality rates ( Faico-Filho et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%